Mohammad Taghi Ghiasi and New Criticism - Hassan ZOKHTAREH (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
By writing several books during three decades, Mohammad Taghi Ghiasi can be said to stand among those who have tried to make the Persian speaking community acquainted with the French New Criticism. He has thus had an undeniable role in creating the Iranians’ first reception of this movement, particularly, in the context of universities. In so doing, he has introduced himself a translator, a researcher, and even a writer although in most of his books, he is no more than a translator of works of French authors. The present study is on the belief that the quality of Ghiasi’s work in this domain has been progressively declining. This falling trend has gone so far that he has sometimes provided his audience with an incorrect, vague, and even misleading image of some new movements in criticism. The origin of such distorted image of literary criticism can be found in his lack of loyalty in translating French texts and in introducing fundamental changes in them. The Persian speaking reader also faces texts which have little similarity with Ghiasi’s so-called books and the introductions he has written to them.